Group Work as a Means of Getting Students to Participate - Forero Tovar Luz Marina (Universidad Nacional de Colombia, 2000)
Three types of activities were worked on with a group of 15 shy and slow 10th grade students at the Centro Educativo Integral Colsubsidio to get them to participate and talk more often and fluently than they were doing. Activities selected for that purpose were : games, role-plays and interviews that had to be carried out in groups. Students' difficulties expressing their ideas fluently rather than accurately were confirmed by means of a questionnaire, then the activities listed above were piloted and the results of their effectiveness were measured by a teacher observer, by my own field notes and by interviews as well as a final questionnaire applied during and at the end of the piloting stage. Results from these three sources were analysed and showed that some students benefited slightly from the activities while others just improved their pronunciation as a result of their work with different partners. Also, some students were not keen on working in groups because they preferred individual work. Speaking ability was not improved as much as expected but the kind of work (group work) helped students to participate more in class. It is also interesting to point out that female students preferred role-plays to the other two activities while male students enjoyed games the most.